A simple technique for bone storage after decompressive craniectomy in children - Sılav, Gökalp; Bölükbaşı, Fatih Han; Özek, Erdinç; Tönge, Mehmet; Onoz, Mustafa; Elmacı, İlhan (Karger, 2014)
Cranial vault reconstruction in the pediatric population is a specialized procedure, which requires additional considerations. Generally, inherent difficulties of bone storage and cranioplasty are neglected in the literature. We present a simple method of bone storage and autologous cranioplasty in a small child with severe head injury. The child underwent surgical treatment with decompressive craniectomy. A bone flap was transversally divided into two pieces and stored under the galea. Bone storage and reconstruction of the cranial vault with our surgical technique is a safe, easy and cost-effective choice excluding the surgical trauma to obtain a new subcutanous pocket for bone storage in pediatric decompressive craniectomy patients.
WOS: 000357861100008
PubMed ID: 25998533
Keywords: Bone Flap Storage; Autologous Cranioplasty; Decompressive Craniectomy